Repositioning Quinacrine Toward Treatment of Ovarian Cancer by Rational Combination With TRAIL - Liang, Rui; Yao, Yuanfei; Wang, Guangyu; Yue, Er; Yang, Guangchao; Qi, Xiuying; Wang, Yang; Zhao, Ling; Zheng, Tongsen; Zhang, Yanqiao; Wenge Wang, Edward (Frontiers in Oncology, 2020)
Quinacrine has been identified as a potent DR5-inducing agent that sensitizes cancer cells to TRAIL-induced apoptosis. In the current study, we found that quinacrine increased DR5 mRNA levels significantly in ovarian cancer cell lines regardless of p53 status. Further study showed the half-life of DR5 in quinacrine-treated cells was significantly prolonged, indicating that DR5 protein degradation was inhibited by quinacrine. We tested if the combination of TRAIL and quinacrine could be effective in ovarian cancer treatment in vitro and in ovarian cancer xenograft mouse models. We found that quinacrine enhanced TRAIL sensitivity or reversed TRAIL resistance in all the ovarian cancer cell lines tested. Mice treated with quinacrine and TRAIL remained disease-free for up to 20 weeks, however, mice treated with TRAIL or quinacrine alone and in control group died within 8 weeks after treatment. Intraperitoneal delivery of quinacrine and TRAIL is rational and practical with extraordinary synergistic anti-cancer effects in preclinical models of ovarian cancer. Clinical investigation of combining quinacrine with TRAIL for ovarian cancer treatment is warranted.